Making Effectiveness Customer Complaint Handling - Rezi Muhamad Taufik Permana; Roro Arinda Reswanti Julian Pratama (Almana : Jurnal Manajemen dan Bisnis, 2020)
The quality of service provided by each Bank becomes a differentiator and becomes a consideration for customers to be loyal to the Bank. With increasing competition in the service and manufacturing sectors, the strategic focus has shifted to determining retention strategies for customers. The speed of handling complaints is measured by SLA (Services Level Agreement), where each bank is required to settle customer complaints a maximum of 20 working days. For this reason, the company has a great responsibility to be able to handle customer complaints following the established SLA (Services Level Agreement). Risk of reputation and even financial risk can arise if customer complaints are not handled quickly and accurately. The research method uses PDCA (plan, do check, action) to know how the business process can be a continuous improvement. This research will show what the effect of complaint handling is too late with the root causes method. To give feedback from the problem this research uses decision-making tools as Analytic Hierarchy Process.